Polyploidy Expands the Range of Centaurium (Gentianaceae) - Maguilla, Enrique; Escudero, Marcial; Jiménez-Lobato, Vania; Díaz-Lifante, Zoila; Andrés-Camacho, Cristina; Arroyo, Juan (Frontiers in Plant Science, 2021)
The Mediterranean region is one of the most important worldwide hotspots in terms of number of species and endemisms, and multiple hypotheses have been proposed to explain how diversification occurred in this area. The contribution of different traits to the diversification process has been evaluated in different groups of plants. In the case of Centaurium (Gentianaceae), a genus with a center of diversity placed in the Mediterranean region, polyploidy seems to have been an important driver of diversification as more than half of species are polyploids. Moreover, ploidy levels are strongly geographically structured across the range of the genus, with tetraploids distributed towards more temperate areas in the north and hexaploids in more arid areas towards the south. We hypothesize that the diversification processes and biodiversity patterns in Centaurium are explained by the coupled formation of polyploid lineages and the colonization of different areas. A MCC tree from BEAST2 based on three nuclear DNA regions of a total of 26 taxa (full sampling, of 18 species and 8 subspecies) was used to perform ancestral area reconstruction analysis in “BioGeoBEARS”. Chromosome evolution was analyzed in chromEvol and diversification in BAMM to estimate diversification rates. Our results suggest that two major clades diverged early from the common ancestor, one most likely in the western Mediterranean and the other in a widespread area including west and central Asia (but with high uncertainty in the exact composition of this widespread area). Most ancestral lineages in the western clade remained in or around the western Mediterranean, and dispersal to other areas (mainly northward and eastward), occurred in the tips. Contrarily, most ancestral lineages in the widespread clade had larger ancestral areas. Polyploidization events in the western clade occurred at the tips of the phylogeny and were mainly tetraploid, while polyploidization events occurred in the widespread clade were at the tips and in an ancestral node of the phylogeny, and were mainly hexaploid. We show how ancestral diploid lineages remained in the area of origin, whereas recent and ancestral polyploidization could have facilitated colonization and establishment in other areas.